Utilização diferencial dos TLR2 e TLR9 pelas células do eixo fagocítico mononuclear durante a infecção aguda por T. cruzi - Humberto Doriguêtto Gravina (2015)
This work highlights the differential use of TLRs by innate immune cells as a central mechanism in the organization of the response against the T. cruzi, the etiological agent of Chagas disease. To this, we had used flow cytometry as a prospecting tool to identify TLR-responsible cells. Also, we had evaluated the inflammatory cytokine synthesis in response to a unique or combinated stimulation by TLR2 and TLR9 agonists (Pam3Cys and CpG DNA, respectively). At first, we noted the involvement of TLR9 in the establishment of a proinflammatory cytokine profile, typical Th1, which was associated with classical dendritic cell (cDC) activity. Then, TLR2 was correlated with a modulated pro- and anti-inflammatory cytokine profile promoted basically by monocytes (Mo) and classical macrophages (Mϕ). In this regard, we identified splenic cDC-MHCIIhiCD11chi, cMϕ-F4/80hiCD11blo, and two types of Mo-F4/80loCD11bhiMHCIIloCD11c+Ly6Chi/loTLR2hi. cDCs and Mϕs were naturally found in the spleen of healthy animals and they synthesized during the infection: IL-12 after TLR9-triggering and TNF-α in a TLR2 dependent way, respectively. Independently on the agonist in medium, the monocyte sets had been shown as sources of pro- and anti-inflammatory cytokines. Mo-Ly6Chi produced proinflammatory cytokines (IL-12 and TNF-α) while Mo-Ly6Clo synthesized IL-10 and TNF-α. We believe that the adaptor molecule MyD88 recruitment is the fundamental step on the proinflammatory role of TLRs while the TLR2 modulatory function is due to the activation of a signaling pathway regulated by Mal/TIRAP. In summary, the cooperation between TLRs was essential to control the T. cruzi replication and involves distinct types of cellular interactions, by modulating: the cellularity of lymphoid organs, receptor expression, use of signaling pathways, and cytokinetic profiles.